Clinical profile and outcome of early onset sepsis in high risk very low birth weight neonates - Shukla, Omprakash S.; Rawat, Aditi (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal sepsis is one of the main causes of mortality and morbidity, especially in very low birth weight neonates (birth weight <1499 grams) despite the progress in hygiene, introduction of new and potent antimicrobial agents for treatment and advanced measures for diagnosis. The aim of the study was to find correlation of clinical features and risk factors of neonatal sepsis in culture positive cases. Methods: A cross- sectional study was carried out in one hundred neonates with risk factors of septicemia after obtaining informed consent. Blood culture was done using Bactec Peds Plus/F Culture as a gold standard to diagnose septicaemia. Correlation of risk factors, clinical features with laboratory findings was obtained by using chi-square test. p-value of less than 0.05 was considered as significant. Results: Out of 100 neonates with suspected sepsis, BACTEC culture proven sepsis was seen in 40% cases. Gram negative sepsis was seen in 62.5% cases. The most common bacteria for early onset sepsis were Klebsiella, Pseudomonas and MRSA contributing 17% each to the bacteriological profile. The most common predisposing factor and clinical feature in culture positive cases were Premature rupture of membrane >24 hours (67%) and bleeding/petechia/pupura (72%) respectively. The major cause of mortality was pulmonary hemorrhage. Conclusions: Gram negative organism were more common and associated with higher mortality. Blood culture positivity increases with increase in number of risk factors in neonatal septicemia. A detailed history and thorough clinical examination is vital for early recognition of sepsis.